Is Agriculture still a Strong Force in Employment Generation in Nigeria? An Empirical Investigation: Array - Tochukwu, Obiakor Rowland; Omoyele, Olufemi Samuel; Olanipekun, Wahid Damilola; Aderemi, Timothy Ayomitunde (EuroEconomica, 2021)
Despite the huge potentials of agriculture and agribusiness in Nigeria, the level of unemployment remains the issue of concern in the country. Therefore, study regarding agriculture and employment creation in Nigeria requires an urgent attention. However, few efforts to provide empirical evidence to justify the above subject matter in past studies have not yielded substantial results. Against this backdrop, this study provided an empirical answer to the question whether the contribution of agriculture has generated employment in the Nigerian economy. Consequently, secondary data was utilized from 1990 to 2019 with the application of Fully Modified Ordinary Least Squares technique and pairwise Granger causality in analysing the collected data. It is instructive to state that agriculture has a significant impact in employment generation in the country because a unit change in agricultural value added reduces unemployment rate by 11% in the country. However, government expenditure on agriculture has not contributed to employment generation in the country because a unit change in this expenditure leads to 0.036% rise in unemployment rate in the country. Furthermore, the results from Granger causality analysis confirmed that no feedback relationship exists between agricultural value added and unemployment rate in Nigeria. In the light of the above findings, this study makes these recommendations for the policy makers in Nigeria, and as well as its counterparts in Africa by extension as follows; generating employment in Nigeria requires that the policymakers embarks on policies that would create value addition to agricultural products in the country. Also, it is expedient that the policymakers in the country should embark on massive investment in agriculture, and as such creation of employment would be facilitated in the long run.